1982
DOI: 10.1148/radiology.145.1.6289375
|View full text |Cite
|
Sign up to set email alerts
|

Work in progress: 252Cf neutron brachytherapy for hemispheric malignant glioma.

Abstract: It has been shown that 252Cf neutron brachytherapy of hemispheric malignant glioma can be readily carried out and may be combined with external, whole brain photon beam therapy of 6,000 rad (60 Gy) administered over a five-week to seven-week period. The ten patients who were studied tolerated both procedures well. There was improvement in performance status, and a decrease in tumor size was observed upon computed tomographic scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Farwell et al (4) reported a mean survival of 9.5 months in cerebellar tumors compared to 14.5 months in cerebral tumors. Since the survival is so poor there have been multiple trials to improve survival results using various treatment modalities, such as hypoxic radiosensitizer (12), neutron beam (13), hyperbaric oxygen (14), brain neutron brachytherapy (15), and multiple daily fractionation radiotherapy (16). There has been prolongation in the median survival when a high dose radiation technique was used compared to low dose radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Farwell et al (4) reported a mean survival of 9.5 months in cerebellar tumors compared to 14.5 months in cerebral tumors. Since the survival is so poor there have been multiple trials to improve survival results using various treatment modalities, such as hypoxic radiosensitizer (12), neutron beam (13), hyperbaric oxygen (14), brain neutron brachytherapy (15), and multiple daily fractionation radiotherapy (16). There has been prolongation in the median survival when a high dose radiation technique was used compared to low dose radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, late tissue reactions may occur whose RBE's are likewise presently unknown and may be very high. While such investigations will be undertaken in studies underway, it is well to note that the prognosis of the cancers treated with Cf-252 was so grave and inevitably fatal that clinical trials were needed if treatment was to be improved [16,19]. Concurrent basic biological studies also need to be carried out since observed tumor responses to neutrons were so different [14,15] that the simple adjustment of a prescribed dose by a RBE value may not only mislead but actually misguide the intent of the planned therapeutic program.…”
Section: Discussionmentioning
confidence: 99%
“…Brain implants were done between 2-4 weeks after surgery after full scalp healing (9). Implant radiotherapy was of several hours (4-8 h) duration and used Cf-252, a radioactive isotope of the transplutonium series which emits fast neutrons of 2.3 MeV average energy (8).…”
Section: Brain Implant and Radiotherapymentioning
confidence: 99%
“…To carry out interstitial therapy, accurate knowledge about tumor site is essential. We are testing Cf for neutron implant radiotherapy for malignant gliomas of the brain (12), a form of therapy which may be much more effective against malignant brain tumors than presently available (9,10). It has been found that MR was an excellent means of imaging the brain and for assessing the extent of tumor.…”
Section: Introductionmentioning
confidence: 99%